Effect of Cognitive Restructuring Technique on Test Anxiety among Secondary School Students in Anambra State (Journal of Guidance and Counselling Studies, 2025)
The quest for a permanent solution to decreasing test anxiety among young people necessitated the study on the  effect of  cognitive restructuring technique on test anxiety among secondary school students in Awka- South L.G. A of Anambra State. two research questions and two null hypotheses tested at 0.05 level of significance guided the study. The study adopted a quasi- experimental design, specifically the pretest posttest non randomized control group.  five hundred and eighty students constituted the population. The sample for the study comprises of one hundred and sixty four senior secondary year one and two (SS1 and SS2) students who are test anxious sampled from three government owned co – educational schools in Awka-South L.G.A  of Anambra State. The sampled students were  assigned to experimental and control groups respectively. The instrument used for data collection was an adopted Speideger test anxiety inventory. The reliability of the instrument was that of internal consistency established using Alpha Cronbach. The experimental group were  taught  cognitive restructuring technique  for eight weeks while the control group were given the conventional counselling. Mean was used for answering the research questions while analysis of covariance (ANCOVA) was used in testing the null hypotheses. The findings of the study revealed cognitive restructuring technique were effective in modifying test anxiety behaviour among secondary school students. Moreover, the findings further revealed that  cognitive restructuring technique was more effective in reducing female secondary school students’ test anxiety behaviour. It was therefore recommended that school counsellors, teachers and psychologists should employ appropriate psychotherapies, particularly cognitive  restructuring technique  in modifying test anxiety of students, teacher training colleges and institutions should emphasize and adopt cognitive restructuring  technique in training pre-service guidance counsellors. Seminars, symposia, workshops, and conferences should be organized for guidance counsellors by the government, education stakeholders and professional bodies like Counselling Association of Nigeria (CASSON) to familiarize guidance counsellors with this innovative technique that can help reduce test anxiety behaviour among student.